(untitled) (Bangladesh Journal of Plant Taxonomy, 2018)
The genus Crinum L. represented by eight species in Bangladesh is revised. The species occurring in Bangladesh are Crinum amabile Donn, C. amoenum Roxb., C. asiaticum L., C. defixum Ker-Gawl., C. jagus (Thomps.) Dandy, C. latifolium L., C. pratense Herb. and C. stenophyllum Baker. Each species is described with updated nomenclature, important synonyms, English and Bangla names, phenology, specimens examined, chromosome number, habitat, distribution, economic value and mode of propagation. A dichotomous bracketed key to the species and illustrations are also provided.